Weathering of Reactive Mineral Phases in Landslides Acts as a Source of Carbon Dioxide in Mountain Belts. Issue 10 (27th October 2018) - Emberson, R.; Galy, A.; Hovius, N.
Abstract: Bedrock landsliding in mountain belts can elevate overall chemical weathering rates through rapid dissolution of exhumed reactive mineral phases in transiently stored deposits. This link between a key process of erosion and the resultant weathering affects the sequestering of carbon dioxide through weathering of silicate minerals and broader links between erosion in active orogens and climate change. Here we address the effect on the carbon cycle of weathering induced by bedrock landsliding in Taiwan and the Western Southern Alps of New Zealand. Using solute chemistry data from samples of seepage from landslide deposits and river discharge from catchments with variable proportions of landsliding, we model the proportion of silicate and carbonate weathering and the balance of sulfuric and carbonic acids that act as weathering agents. We correct for secondary precipitation, geothermal, and cyclic input, to find a closer approximation of the weathering explicitly occurring within landslide deposits. We find highly variable proportions of sulfuric and carbonic acids driving weathering in landslides and stable hillslopes. Despite this variability, the predominance of rapid carbonate weathering within landslides and catchments where mass wasting is prevalent results at best in limited sequestration of carbon dioxide by this process of rapid erosion. In many cases where sulfuric acid is a key weathering agent, a net release of CO2 to the atmosphere occurs. This suggests that a causal link between erosion in mountain belts and climate change through the sequestration of CO2, if it exists, must operate through a process other than chemical weathering driven by landsliding. Key Points: Landsliding elevates dissolution of highly reactive mineral phases in rapidly eroding mountain belts In Taiwan, this process leads to extensive dissolution of sulfides and carbonate rock The net effect is to release carbon dioxide, inverting the commonly assumed negative feedback on chemical weathering via higher erosion Plain Language Summary: There is a long‐standing debate surrounding the link between erosion and climate. It is often suggested that as temperatures increase, rainier and stormier weather could increase erosion of rock; as that rock is exposed, silicate minerals within could break down, which, on long time scales, can remove CO2 from the atmosphere, lowering global temperatures and acting as a negative feedback. Recent studies have shown that landslide deposits are key locations for the link between chemical weathering and physical erosion in some mountain belts. To test how landslides affect the erosion‐climate link, we used samples of water seeping through landslides in Taiwan and New Zealand to calculate the amount of carbon dioxide that is either absorbed or released through this chemical reaction. We find that the large amount of freshly exposed rock in Taiwanese landslide deposits contains significant carbonate rock and sulfide minerals; the net result of the weathering of these minerals is a release of carbon dioxide, which inverts the traditional perspective on the role erosion plays in controlling carbon dioxide release. In some mountain belts, it seems that increased erosion and resulting landsliding may act to increase carbon dioxide in the air, opening further questions into the nature of erosional‐climatic links.